A Study on Consumer Perception of Copper Bottles with Reference to Hyderabad city - MM Quazzafi, Mr.; Geeta Kesavaraj, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Businesses benefit from eco gracious wherein general trends of lucidity, connectivity, and expanded familiarity with maintainability issues add to the general benefit of promoting messages. The customers are expecting and demanding the sustainability-oriented products in a world more candidly involved with health concerns. Â Currently, eco-friendly have an excellent opportunity to gain market grip and increase the consumer base. In coming days, eco -friendly will be a necessary aspect of the commercial world. Copper is your friendly neighbourhood superhero as far as its benefits are considered, not just to the human body, but to the environment too. It is a cheap metal, available in abundance as well as easiest to recycle. There are several benefits of copper, here are some to our health and our environment at large. Despite all the benefits of copper, one must remember that copper is only required in trace amounts in the human body. One must also remember that too much of a good thing could also become harmful, especially, if we are talking about the delicate balance of the human chemistry. Water makes 75% of our anatomy, however, one cannot keep on drinking water stored in copper vessel, all day and every day. In the above context the aim of the research is to examine the perception of buyers towards copper water bottles in Hyderabad. Data were collected through questionnaire survey of 50 customers of Hyderabad based on convenient sample. A Chi-Square test were employed to the test Association between awareness and usage of copper bottles, benefits and usage of copper bottle and effects and usage of copper bottle.Â Â